Volatile Data Acquisition and Analysis by Using Memory Forensics Techniques - Rabia Mehmood (International Journal for Electronic Crime Investigation, 2023)
Memory forensics is a vital component of digital investigations, involving the analysis of volatile memory (RAM) in computer systems to gather evidence, identify malicious activities, and reconstruct cybercrime incidents. This paper provides an overview of memory forensics, highlighting its defini-tion, importance, purpose, and scope. It explores the evolution and significance of memory forensics in response to increasingly complex cyber threats. The memory forensics process is discussed, cover-ing memory acquisition and analysis. Legal and ethical considerations related to the admissibility of memory evidence and privacy protection are examined. The paper also discusses the types of memory, including physical and virtual memory, and their characteristics and significance in memory forensics. Furthermore, it explores the memory acquisition process, different methods, tools, and techniques used, as well as the importance of preserving evidence integrity. Finally, the paper introduces various tools for memory analysis, such as Volatility, Volatility Workbench, FTK Imager, Encase, Hibernation Recon, and Xplico, and highlights their role in extracting valuable evidence from memory dumps.